(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Coolie is a study in destitution, or to use Peter Quennell’s words: ’India seen third-class—a continent whose bleakness, vastness and poverty are unshaded by a touch of the glamour more or less-fictitious, that so many English story-tellers, from Kipling to Major Yeats-Brown, have preferred to draw across the scene.’ The novel relates a series of adventures in picaresque manner, only the hero is no rouge but himself the victim of the world’s rogueries. Unlike Bakha, the negative hero of Untouchable it is not his place in the old caste system that is questioned because he belongs by birth to the second highest order. What is questioned is his place in the new caste system, on the basis of cash nexus, that the Kalying has established.